CEU Graduation Ceremony 2003 (edited) - Part 2
Continuation of the annual CEU Graduation Ceremony held on Wednesday, June 18, 2003 in the Vigadó Hall in the center of Budapest. This part continues with the conferring of the Master’s and doctoral degrees to the MA and PhD candidates of the year 2002/2003. Contains also the presentation of the awards to outstanding Master's graduates from each academic department and program. The moving of the tassels is included here after presenting a short part of the commencement address delivered by the former president of Brazil, Fernando Henrique Cardoso. The ceremony ends with the academic recessional. Scenes from the reception following the ceremony are included.